ADVERTISEMENTS, PRICES, AND ELECTRONIC WORD OF MOUTH ON THE INTEREST OF USERS OF THE GOJEK (GORIDE) APPLICATION SERVICES, DEPOK, WEST JAVA - Ependi, Ependi; Sriyadi, Sriyadi (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to determine the influence of Advertising, Price, and Electronic Word of Mouth (Ewom) on User Interest among Gojek Indonesia consumers in the Depok area. A quantitative method was used, with a Slovin sample of 95 respondents. Advertising influences User Interest, as indicated by a significance value of 0.016 < 0.05 and a t-value of 2.260 > 1.986. Price also affects User Interest, with a significant value of 0.001 < 0.05 and a t-value of 3.373 > 1.986. Additionally, Ewom has an impact on User Interest, as shown by a significant value of 0.02 < 0.05 and a t-value of 3.085 > 1.986. The F-test results indicate that Advertising, Price, and Ewom collectively influence User Interest, as the calculated F-value exceeds the F-table value (10.574 > 2.70). The extent of the independent variables' influence on the dependent variable is positive, with an R-Square value of 0.420 or 42%. There is a significant effect of Advertising, Price, and Ewom on User Interest among Gojek respondents in this study. Therefore, the company is expected to continuously improve its services for consumers, create engaging advertisements, maintain competitive pricing, and address customer and driver complaints effectively, especially those conveyed through Ewom.